Understanding protein diffusion on force-induced stretched DNA conformation - Mondal, Anupam; Bhattacherjee, Arnab (Frontiers in Molecular Biosciences, 2022)
DNA morphology is subject to environmental conditions and is closely coupled with its function. For example, DNA experiences stretching forces during several biological processes including transcription and genome transactions that significantly alters its conformation from that of the B-DNA. Indeed, a well-defined 1.5 times extended conformation of dsDNA, known as $Σ$-DNA, has been reported in DNA complexes with proteins such as Rad51 and RecA. A striking feature in $Σ$-DNA is that the nucleobases are partitioned into triplets of three locally stacked bases separated by an empty rise gap of $\sim 5$ Å. The functional role of such a DNA base triplet was hypothesised to be coupled with the ease of recognition of DNA bases by DNA binding proteins (DBPs) and the physical origin of three letters (codon/anti-codon) in the genetic code. However, the underlying mechanism of base-triplet formation and the ease of DNA base-pair recognition by DBPs remain elusive. To investigate, here we study the diffusion of a protein on a force induced stretched DNA using coarse-grained molecular dynamics simulations. Upon pulling at the 3$^′$ end of a DNA by constant forces, the DNA exhibits a conformational transition from B-DNA to a ladder-like S-DNA conformation via $Σ$-DNA intermediate. The resulting stretched DNA conformations exhibit non-uniform base pair clusters such as doublets, triplets, quadruplets etc., among which triplets are energetically more stable than others. We find that protein favours the triplet formation while interacting non-specifically along DNA and the relative population of it govern the ruggedness of the protein$-$DNA binding energy landscape and enhances the efficiency of DNA base recognition. Furthermore, we analyse the translocation mechanism of a DBP under different force regimes and underscore the significance of triplets formation in regulating the facilitated diffusion of protein on DNA. Our study, thus, provides a plausible framework for understanding the structure-function relationship between triplet formation and base recognition by a DBP and helps to understand gene regulation in complex regulatory processes.